CsCBDAS2-Driven Enhancement of Cannabinoid Biosynthetic Genes Using a High-Efficiency Transient Transformation System in Cannabis sativa ‘Cheungsam’ - Sang-Cheol Baek; Sang-Yoon Jeon; Bo-Hyun Byun; Da-Hoon Kim; Ga-Ram Yu; Hyuck Kim; Dong-Woo Lim (Plants)
Cannabis sativa produces pharmacologically valuable cannabinoids. In this study, we developed and optimized a transient transformation system using Cannabis sativa ‘Cheungsam’ to facilitate gene functional analysis. Various experimental conditions, including plant developmental stages, light conditions, Agrobacterium strains, tissue types, and physical treatments such as sonication and vacuum infiltration, were systematically evaluated using GUS histochemical staining and qPCR analysis. Among these, 7-day-old seedlings cultured under dark conditions and transformed with the GV3101 strain exhibited high transformation efficiency. Leaf tissue showed a higher GUS staining proportion and GUS staining area compared to hypocotyl and cotyledon tissues. The application of a combination of sonication and vacuum infiltration techniques resulted in the most intense GUS expression. Using the optimized protocol, we introduced a recombinant vector carrying CsCBDAS2, a key gene in cannabidiol (CBD) biosynthesis. qPCR analysis revealed that CsCBDAS2 overexpression led to significant upregulation of multiple upstream CBD biosynthetic genes (CsOAC, CsGOT, CsPT1, CsPT4, CsCBDAS1, and CsCBDAS2) and the transcription factor (TF) CsWRKY20, suggesting coordinated co-expression and potential involvement of a transcriptional feedback loop. These results demonstrate the effectiveness of our transient transformation system and provide insights into the regulatory mechanisms of cannabinoid biosynthesis in cannabis.